Occurrence and variation of calcium oxalate crystals in selected medicinal plant species - Capacio, Alyssa Faye Z.; Belonias, Beatriz S. (Annals of Tropical Research, 2018)
Calcium oxalate (CaOx) crystals are microscopic mineralized particles found in over 215 plant families of plants. In this study, the occurrence and variation of CaOx crystals in 15 different species of commonly used medicinal plants were investigated. Information on the type and other characteristics of CaOx crystals present in medicinal plants is important considering the potential health risks posed by these crystals to humans and other animals, aside from the fact that crystal characteristics are also valuable in the taxonomic identification of plant taxa. Results showed that eight of the 15 species, namely; Abelmoschus esculentus, Acalypha indica, Amaranthus viridis, Basella alba, Bixa orellana, Codiaeum variegatum, Ipomoea batatas, and Jatropha podagrica produced druses. Only four species formed raphides and these were Bougainvillea spectabilis, Cordyline fruticosa, Impatiens balsamina, and Rhoeo spathacea, although styloids were also observed in Cordyline fruticosa. Prismatic crystals and crystal sands were the least common, the former produced only in Chorchorus olitorius and Senna alata, and the latter only in Solanum melongena. The raphides of B. spectabilis were the longest at 175.81µm while the druses of B. orellana were the smallest having a mean diameter of 16.72µm. In terms of density, C. olitorius and S. alata had the highest number of crystals per unit leaf area.